2002
DOI: 10.1177/026988110201600410
|View full text |Cite
|
Sign up to set email alerts
|

The potential cardiotoxicity of antipsychotic drugs as assessed by heart rate variability

Abstract: Most antipsychotic drugs have cardiac effects as a consequence of their pharmacological actions. Recently, thioridazine has been subjected to a restricted indications notice and sertindole had its license withdrawn because of concerns about their potential cardiotoxicity. In the development of new atypical agents, heart-rate corrected QT effects are evaluated but it is unclear how predictive these are of clinically significant cardiotoxicity or sudden death. Heart rate variability (HRV) is a potential index of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 39 publications
1
31
1
2
Order By: Relevance
“…Although no correlation between cardiovagal function and antipsychotic use was identified, antipsychotic use may still exacerbate autonomic dysfunction [15], [16]. The impact of long-term antipsychotic use on autonomic modulation of chronic patients as well as its relationship with cardiac toxicity deserve further investigation [59]. Our results showed no association between the patient's functioning and lower measures of HRV, which were different from Fujibayashi et al 's findings [10].…”
Section: Discussioncontrasting
confidence: 91%
“…Although no correlation between cardiovagal function and antipsychotic use was identified, antipsychotic use may still exacerbate autonomic dysfunction [15], [16]. The impact of long-term antipsychotic use on autonomic modulation of chronic patients as well as its relationship with cardiac toxicity deserve further investigation [59]. Our results showed no association between the patient's functioning and lower measures of HRV, which were different from Fujibayashi et al 's findings [10].…”
Section: Discussioncontrasting
confidence: 91%
“…Our results did not show any obvious increase in HRV in the olanzapine group, and the hypothesis of improvement of cardiac heart function was not supported by the results of our study. Another possible explanation is that co-medication with benzodiazepine (in 12 of 18 patients in the olanzapine group) may cause a reduction in central vagal tone [25] ; however, similar results were not obtained in another study [17] .…”
Section: Discussionmentioning
confidence: 75%
“…Another study reported that olanzapine increased HRV in healthy male volunteers and, in a short-term evaluation [17] , they concluded that olanzapine may improve cardiac heart function; however, we should treat this conclusion with caution, as single-dose short-term observations in healthy males may not provide evidence of a reliable index for use in schizophrenia patients. Our results did not show any obvious increase in HRV in the olanzapine group, and the hypothesis of improvement of cardiac heart function was not supported by the results of our study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The bulk of the existing literature examining antipsychotic drug effects on HRV has focused on samples with schizophrenia, and the results have been generally inconclusive with exposure variably defined (Bar et al , 2008a; Chang et al , 2010; Cohen et al , 2001; Hempel et al , 2009; Latalova et al , 2010; Malaspina et al , 2002; Mujica-Parodi et al , 2005; Silke et al , 2002; Wang et al , 2008). Several studies found a negative correlation between AP exposure and parasympathetic activity (Bar et al , 2008a; Mujica-Parodi et al , 2005).…”
Section: Introductionmentioning
confidence: 99%